All Days 2008
DOI: 10.2118/112186-ms
|View full text |Cite
|
Sign up to set email alerts
|

Production Optimization: System Identification and Uncertainty Estimation

Abstract: 1 Abstract Real-time optimization of oil and gas production requires a production model, which must be fitted to data for accuracy. A certain amount of uncertainty must typically be expected in production models fitted to data due to the limited information content in data. It is usually not acceptable to introduce additional excitation at will to reduce this uncertainty due to the costs and risks involved. The contribution of this paper is twofold. Firstly, this paper discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…In Bieker et al (2007) it has been proposed that uncertainty in production optimization should be related to production profit to allow structured business cases for uncertainty mitigation to be created. Elgsaeter et al (2008) suggested how uncertainty due to low information content in production data can be quantified using bootstrapping. No references have been found which discuss the value of information in the context of daily oil and gas production optimization.…”
Section: Prior Workmentioning
confidence: 99%
See 3 more Smart Citations
“…In Bieker et al (2007) it has been proposed that uncertainty in production optimization should be related to production profit to allow structured business cases for uncertainty mitigation to be created. Elgsaeter et al (2008) suggested how uncertainty due to low information content in production data can be quantified using bootstrapping. No references have been found which discuss the value of information in the context of daily oil and gas production optimization.…”
Section: Prior Workmentioning
confidence: 99%
“…where w[t] is a user-specified weighting function. When Z N has low information content, it may not be possible to determineθ uniquely from (12), resulting in an uncertainty inθ that can be quantified in terms of a probability density function f θ (θ)u s i n gbootstrapping,s e eE f r o na n d Tibshirani (1993) or Elgsaeter et al (2008). Bootstrapping is a computational approach which generates an estimate of uncertainty by re-solving (12) a number of times to fit the model to number of synthetically generated, or "re-sampled", data sets similar to (10).…”
Section: Prerequisitesmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2006, the method combining empirical formula with optimization theory is proposed by Saputelli [3,4], Elgsaeter [5], and Awasthi [6] and etc. Their goal focused on the short-term optimization of production and gained the optimized development program in time with convenient empirical formula.…”
Section: Introductionmentioning
confidence: 99%